Facial Expression Detector While Driving - Wefa, Indah Dara; Mukhaiyar, Riki (Jurnal Teknik Elektro Indonesia, 2024)
Facial expression when a person is sleepy can be seen from eye behavior and facial behavior. To detect the driver's drowsiness, facial expression is a form of non-verbal communication that results from one or more facial muscle movements that can indicate a person's emotional state. This detector works automatically when the system runs without external control. The system is controlled only via the desktop using the Convolutional Neural Network (CNN) method. The working principle of this tool is to start by connecting the power when the system and the Desktop are turned on, then activate the Open CV software created on the desktop and continue testing to recognize the driver's face. If the detected face has a sleepy expression, the device will show the driver's drowsiness through the speaker and warn the driver to be careful when driving. The test results show that the system can detect drowsiness optimally. With the existence of this tool, it is hoped that it can reduce the death rate due to traffic accidents by preventing the driver from experiencing the sleep phase while driving.